HUBUNGAN ANTARA KESEPIAN DENGAN PERILAKU CYBERBULLYING PADA REMAJA DI MAN 2 TANAH DATAR - Putri, Yulia Rahmat (Batanang : Jurnal Psikologi, 2025)
This study aims to determine the relationship between loneliness and cyberbullying behavior in adolescents at MAN 2 Tanah Datar. The research method used is a quantitative research method with a correlational research type. Based on the results of the hypothesis shows that (rxy = -0.559) with a significance value of 0.01. This means that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. This shows that there is a significant relationship between loneliness and cyberbullying behavior in adolescents at MAN 2 Tanah Datar. The results of the study showed that there was a positive relationship between loneliness and cyberbullying behavior, meaning that the higher the level of loneliness in adolescents, the higher the likelihood that they will be involved in cyberbullying behavior. Conversely, adolescents who feel less lonely tend to show lower cyberbullying behavior